Prevalence of obesity-associated with health issues among Koya Technical Institutes Staff in Kurdistan Region, Iraq - Abdullah, Saman R.; Saleh, Kochar Kh.; Khudhir, Karwan M.; Mahmood, Kocher A.; Hamarashid, Bahra R. (Salahaddin University - Erbil, 2021)
The obesity rate and its prevalence are increasing with many complications in the population. Obesity is a condition in which the bodyweight gain extended to the point where it causes obstacles to health. Usually, this extended body weight comes from excessive fat which consequences of the imbalance between calories expended and calories consumed. Pre-test questionnaire by utilizing validation of self-administration as a cross-sectional investigation was carried out to diagnose the overview of obesity and health issue risks among Koya technical staff. The height of the staff was calculated by supporting a measuring tape (Seca 206 body meter) and the mass of the body (kg) was measured by providing weighing scale TANTA. Overall, according to the findings of this study, we conclude that body overweight (54.7%) and obesity (18%) are clear among academics and administrate staff of Koya Technical Institute at Erbil Polytechnic University. While normal body weights are (25.3%) and underweight approximately (2%). Analyses of data showed that obesity is a significant difference between married and unmarried of participants, besides, there are many factors appear to have a great role and association with health situation and body overweight such as (age, gender, and level of education, type of work, income and physical activity). Physical activities and lifestyle have a strong relation with obesity, especially its reveal among administrates rather than academics, because of fewer activities and lack of regular exercise. © 2021, Salahaddin University - Erbil. All rights reserved.
Keywords: Health issues; Obesity; Prevalence; Risk factors